Habitat Distribution, Habitat Characteristics And Behaviour Of The Black Giant Squirrel (Ratufa Bicolor Penangensis) In Penang Island - Kasim, Najwa (2012)
The Black Giant Squirrel (Ratufa bicolor penangensis) is listed as a totally protected species under the Malaysian Wildlife Conservation of Act (2010) and classified as protected species under the international law such as IUCN by the loss of its habitat. A study on the Black Giant Squirrel’s distribution, habitat selection, daily movement and behaviour was conducted in Penang Island, from January 2008 to October 2009, to obtain baseline information for the species. Surveys on habitat distribution and habitat characteristics such as latitude, longitude, elevation, tree height, and Girth at Breast Height (GBH) were measured and recorded. Land use map was generated to analyse the squirrel’s habitat locations by using remote sensing and Geographic Information System (GIS).